Alterations of cholesterol precursor levels in Alzheimer's disease - Kölsch, Heike; Heun, Reinhard; Jessen, Frank; Popp, Julius; Hentschel, Frank; Maier, Wolfgang; Lütjohann, Dieter (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2010)
Cerebral and extracerebral cholesterol metabolism are altered in Alzheimer's disease (AD) as indicated by reduced plasma levels of the cholesterol elimination products 24S-hydroxycholesterol, which is of cerebral origin, and of 27-hydroxycholesterol, which is formed extracerebrally. However, it has to be evaluated, if changes of cholesterol metabolism in the whole body or in the CNS are exclusively due to the altered elimination of cholesterol or are also due to altered de novo synthesis in AD. We investigated CSF and plasma levels of cholesterol and of its precursors lanosterol, lathosterol and desmosterol in AD patients and non-demented controls. We found CSF levels of cholesterol (p=0.011), absolute levels of all investigated cholesterol precursors (each p<0.001) and ratios of cholesterol precursors/cholesterol (each <0.01) to be lower in AD patients as compared to controls. In plasma, the absolute levels of lanosterol (p=0.026) and lathosterol (p<0.001) and the ratio of lathosterol/cholesterol (p=0.002) but none of the other investigated parameters were reduced in AD patients (p>0.1). Furthermore, ratios of desmosterol/lathosterol in CSF (p=0.023) and plasma (p=0.009) were higher in AD patients as compared to controls. Our data support the hypothesis that cholesterol metabolism is altered in AD and further suggest that especially cholesterol de novo synthesis within the CNS of AD patients might be reduced. These findings raise doubt on a beneficial effect of cholesterol lowering treatment in manifest AD.